The Effect of Kurdistan Newspaper in Spreading National Awareness – An Analytical Study - Pave Jamil Ahmed (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
The media have great influence on many aspects of the community and everyday life of people, in this perspective we can say media is an essential means for communication between the people, in this way we can deal in with the media as social phenomenon. This study divided into some parts, first part discusses the methodology and methods of the study, which includes, methodology research problem, important of the study, the key aims of the study, determine the key concept and terms. The second part of the study will focus on the history of Kurdish journalism and connected to the concept of Kurdish nationalism, the impact of the newspaper on this aspect of the community. In the third part of the study will concentrate on begin of the Kurdish newspaper, the impact of media on publishing on the nationalism awareness. Also, the research will focus on the role of the newspaper in publishing in depth information about the cultural, nationalism, and heritage of the Kurdish community. At the end of this study, I will present key finding and conclusion.